Omeprazole and lansoprazole enantiomers induce CYP3A4 in human hepatocytes and cell lines via glucocorticoid receptor and pregnane X receptor axis - Novotna, Aneta; Dvorak, Zdenek (PloS one, 2014)
Benzimidazole drugs lansoprazole and omeprazole are used for treatment of various gastrointestinal pathologies. Both compounds cause drug-drug interactions because they activate aryl hydrocarbon receptor and induce CYP1A genes. In the current paper, we examined the effects of lansoprazole and omeprazole enantiomers on the expression of key drug-metabolizing enzyme CYP3A4 in human hepatocytes and human cancer cell lines. Lansoprazole enantiomers, but not omeprazole, were equipotent inducers of CYP3A4 mRNA in HepG2 cells. All forms (S-, R-, rac-) of lansoprazole and omeprazole induced CYP3A4 mRNA and protein in human hepatocytes. The quantitative profiles of CYP3A4 induction by individual forms of lansoprazole and omeprazole exerted enantiospecific patterns. Lansoprazole dose-dependently activated pregnane X receptor PXR in gene reporter assays, and slightly modulated rifampicin-inducible PXR activity, with similar potency for each enantiomer. Omeprazole dose-dependently activated PXR and inhibited rifampicin-inducible PXR activity. The effects of S-omeprazole were much stronger as compared to those of R-omeprazole. All forms of lansoprazole, but not omeprazole, slightly activated glucocorticoid receptor and augmented dexamethasone-induced GR transcriptional activity. Omeprazole and lansoprazole influenced basal and ligand inducible expression of tyrosine aminotransferase, a GR-target gene, in HepG2 cells and human hepatocytes. Overall, we demonstrate here that omeprazole and lansoprazole enantiomers induce CYP3A4 in HepG2 cells and human hepatocytes. The induction comprises differential interactions of omeprazole and lansoprazole with transcriptional regulators PXR and GR, and some of the effects were enantiospecific. The data presented here might be of toxicological and clinical importance, since the effects occurred in therapeutically relevant concentrations.
Keywords: hepatocyty; Receptors, Glucocorticoid; pregnanový X receptor; Cytochrome P-450 CYP3A; Hep G2 Cells; buňky Hep G2; receptory glukokortikoidů; Anti-Ulcer Agents; Lansoprazole; lidé; cytochrom P-450 CYP3A; kultivované buňky; protivředové látky; Hepatocytes; Cells, Cultured; Pregnane X Receptor; lanzoprazol; Receptors, Steroid; Omeprazole; steroidní receptory; omeprazol; Humans